β-GLUCAN-INDOMETHACIN COMBINATION PRODUCES NO LETHAL EFFECTS - Vetvicka, Vaclav; Vetvickova, Jana (Biomedical papers, 2009)
Background: The most important quality of β-glucans and the reason why so much attention has been devoted to them are their physiological effects. They are typical biological response modifiers with pronounced immunomodulating activity. However, some questions about possible side effects remain.Aim: Several papers reported the lethal side effects of non-steroidal anti-inflammatory drugs in glucan-treated mice, probably due to the peritonitis by enteric bacteria. However, these results were never independently confirmed. The purpose of this study is to evaluate these claims using several different types of glucans.Methods: Effects of combined treatment with four different types of glucans and indomethacin were measured by evaluation of phagocytosis of HEMA particles by peripheral blood leukocytes and production of IL-6 in mouse serum. In addition, the level of blood glucose, colon length and survival after 30 days of treatment was measured.Results: Our finding showed that simultaneous treatment with glucan and indomethacin caused a small decrease of phagocytic activity and IL-2 production. Two other tested parameters-blood glucose levels and colon length-that had been found to be significantly affected by this treatment, were virtually unchanged. In the final, yet most important part of the study, we found absolutely no mortality, regardless of the type of glucan or the routes of glucan administration.Conclusion: No adverse negative effects due to simultaneous treatment with glucan and non-steroidal anti-inflammatory drug dose was found, despite testing two different routes of glucan administration and four different types of glucan.
Keywords: Glucan/Indomethacin/Adverse effects/Phagocytosis/IL-6/Glucose